Transformasi Digital Dalam Praktik Keagamaan: Penerapan Augmented Reality Berbasis Filter Facebook Melalui Meta Spark Studio Dalam “Menggali Kehidupan Nabi Melalui Filter Facebook” - Muhammad Firasy Sajidan Arifin; Nabila Nur Athiyah; Azmi Aldi Syahrial; Arba Adhy Pamungkas; Zamzam H. K. Mugraha (Jurnal Teknologi Informasi dan Komunikasi, 2022)
In recent years, technological advances have penetrated various aspects of society, including religious practices. Augmented reality is a form of technology that combines the virtual world and the real world, and augmented reality is known as part of a virtual environment or virtual reality (VR) technology[1] . Augmented Reality (AR) is a technology that has great potential to enhance the religious experience and facilitate a deeper understanding of the Islamic religion. Creativity in designing works is developed using augmented reality to become an interactive design tool [2]. This research studies the application of Facebook filter-based augmented reality (AR) through Meta Spark Studio in religious practices, especially in studying the questions asked to the Prophet. Use of these filters allows users to view and interact with digital reconstructions of the questions, providing context and better understanding.